Monitoring of indicators of physical availibility and socio-economic affordability of metformin hydrochloride medicines - Ryshchenko, Oksana; Lytkin, Dmytro; Podolsky, Illya; Volkova, Alina; Vladymyrova, Inna (ScienceRise: Pharmaceutical Science, 2022)
The aim of the study was to monitor the physical availability and socio-economic affordability of metformin hydrochloride medicines, which are used for the treatment of type II diabetes mellitus. Materials and methods. Medical and technological documentation on the standardization of medical care for patients with type II diabetes, data from the State Register of Medicinal Products of Ukraine, software complex “Apteka” of the company “Morion” and data from the pharmaceutical market research analytical company “Pharmstandard” of the company “Morion” were used as research materials to determine indicators of physical availability and socio-economic affordability of metformin HCL medicines for the treatment of type II diabetes. Documentary, analytical methods, the method of marketing research and the method of logical summarization of data were used during the research. Results. According to the results of the analysis of the medical and technological documentation on the standardization of medical care for diabetes mellitus (DM) type II and the State Register of Medicines of Ukraine, a number of characteristics were formed for Metformin HCL pharmaceuticals, namely: tablets or film-coated tablets in a dose of 500 mg, which are manufactured: Ukrainian manufacturers (full cycle of production); Ukrainian manufacturers of tablets in bulk (primary and secondary packaging) and foreign manufacturers. The specified characteristics became the basis for the further selection of several metformin HCL medicines in terms of determining their indicators of physical availability and socio-economic affordability. When determining the physical availability of metformin HCL medications, it was established that Ukrainian-made pharmaceuticals (full production cycle) are presented in the wholesale chain of the pharmaceutical market in full. According to the socio-economic indicator of the solvency adequacy of payment capacity, among the metformin HCL pharmaceuticals, the most economically justified are the Ukrainian-made pharmaceuticals, which are made from tablets in bulk according to the full production cycle. Only 1 medicine was singled out among foreign-made ones, which has the lowest indicator of solvency adequacy for various categories of the population. Conclusions. Monitoring of indicators of physical availability and socio-economic affordability of metformin HCL medicines showed that the most economically justified for able-bodied people and people of retirement age is the use of the Ukrainian-made pharmaceuticals (full cycle and production from tablets in bulk) for the treatment of type II DM)